MINIMUM AND FIXED RESALE PRICES IN VERTICAL AGREEMENTS IN COMPETITION LAW OF THE EUROPEAN UNION - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Resale price maintenance represents a special type of vertical restraint in a vertical agreement, in which an upstream undertaking defines, controls or restricts the price at which a downstream undertaking can resell its product. According to the Commission Regulation (EU) 2022/720 on the application of Article 101(3) of the Treaty on the Functioning of the European Union to categories of vertical agreements and concerted practices the exemption shall not apply to vertical agreements which, directly or indirectly, in isolation or in combination with other factors under the control of the parties, have as their object the restriction of the buyer’s ability to determine its sale price, without prejudice to the possibility of the supplier to impose a maximum sale price or recommend a sale price, provided that they do not amount to a fixed or minimum sale price as a result of pressure from, or incentives offered by, any of the parties. Minimum or fixed resale price maintenance represents a hardcore restriction and as such removes the benefit of the block exemption provided for in Art. 2 of the Regulation 2022/720. The paper deals with the legal regulation of restrictive vertical agreements in which a fixed or minimum resale price is determined in the competition law of the European Union, as well as the methods for such resale price maintenance. The problem will be considered through the analysis of relevant sources of law, practice of the European Commission and the Court of Justice of the European Union and doctrinal views.